More the Tweets More the Citations: Do Altmetric Variables Contribute to Citations? - Ravikumar, S. (Journal of Information and Knowledge, 2017)
The present study was carried out to examine the alternative metrics variables twitter and its relationships with citation pattern for scholarly articles. This study was carried on with top 100 twitted articles for the year 2014-15 and the second set of data was specific to the “Genomic” subject domain, around 131 hot paper was identified and their twittes and citation data was studied. From the study it was found that the top tweeted articles did not have any kind of correlation with citation its ϐ value was 0.071. While the second set of data from the “Genomic” subject showed a strong positive linear correlation between the Twitter count and Citation counts its ϐ value was 0.72.